A physical barrier long-acting disinfectant and a preparation process thereof

CN122873565APending Publication Date: 2026-10-09PACOS BIOTECHNOLOGY (FUJIAN) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611016570.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-09
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0004]为了解决上述技术问题,本发明提供一种物理屏障作用长效型消毒液及其制备工艺,以解决现有技术中消毒时所有人员必须离场,操作系统要有防护措施,消毒后异味不能很快消除,长期使用会对人体有蓄积中毒的危险等问题

Benefits of technology

1、本发明制备的消毒液适用于多种场景,如物体表面、织物、空气等,对化脓性球菌、人冠状病毒及流感病毒等微生物有效,通过在研磨过程中持续通入冷却水循环,防止局部过热导致成分失活,通过纳米研磨与硅烷偶联技术构建双重防护体系;本发明通过食品级硅羟基PA活性复合锌在硅烷偶联剂作用下,于物体表面形成具有纳米级凹凸结构的物理屏障膜,利用范德华力破坏微生物细胞膜,结合苯扎氯铵的协同杀菌作用,实现99.9%的即时杀菌率和72小时长效抑菌效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122873565A_ABST
    Figure CN122873565A_ABST
Patent Text Reader

Abstract

The application provides a physical barrier long-acting disinfectant and a preparation process thereof, which is prepared from the following raw materials in parts by weight: food-grade silicon-hydroxyl PA active composite zinc 0.5-2 parts, deionized water 80-95 parts, silane coupling agent 0.5-2 parts, dispersing agent 0.5-1 part, anti-settling agent 2-4 parts, benzalkonium chloride 0.04-0.05 part, thickening agent 0.5-1 part and defoaming agent 0.5-1 part; the application adopts distributed grinding and gradient stirring to ensure that the dispersion degree of the composite zinc particles reaches the micro-nano level, and after precision filtration through a filter screen, the stability of the product is improved by 40%, and the film forming adhesion is enhanced by 35%; the disinfectant has no irritating odor and no damage to the skin mucosa, and can be widely applied to medical treatment, food processing, home and other scenes, and effectively solves the technical problems of short time effect and easy drug resistance of traditional disinfectants.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of disinfectants, specifically a long-lasting disinfectant with physical barrier function and its preparation process. Background Technology

[0002] Traditional disinfectants mostly rely on chemical bactericides, which have problems such as short-lasting effects, strong corrosiveness, and easy induction of drug resistance. They are toxic, irritating, corrosive to metals, have poor lasting effects, short stability time, and many themselves constitute pollutants. Moreover, all personnel must leave the area during disinfection, the operating system must have protective measures, odors cannot be eliminated quickly after disinfection, and long-term use may pose a risk of cumulative poisoning to the human body.

[0003] In summary, this invention provides a long-lasting disinfectant with physical barrier function and its preparation process to solve the above-mentioned problems. Summary of the Invention

[0004] To address the aforementioned technical problems, this invention provides a long-lasting disinfectant with physical barrier properties and its preparation process, thereby resolving issues such as the requirement for all personnel to leave the site during disinfection, the need for protective measures in the operating system, the inability to quickly eliminate odors after disinfection, and the risk of cumulative poisoning from long-term use in existing technologies.

[0005] A long-lasting disinfectant with physical barrier function is composed of the following raw materials in parts by weight: 0.5-2 parts of food-grade silanol-hydroxyl PA active composite zinc, 80-90 parts of deionized water, 0.5-2 parts of silane coupling agent, 0.5-1 part of dispersant, 2-4 parts of anti-settling agent, 0.04-0.05 parts of benzalkonium chloride, 0.5-1 part of thickener and 0.5-1 part of defoamer.

[0006] The food-grade silanol-hydroxyl PA active composite zinc is a composite microparticle with active zinc ions loaded onto a porous silica matrix through in-situ synthesis technology; wherein the zinc element accounts for 15% to 25% by mass, and the specific surface area is not less than 300 m². 2 / g, particle size distribution is controlled within the range of D50=200~500nm; silanol refers to the large number of active silanol groups on the surface of composite microparticles, PA activity refers to the active sites that enhance the interfacial bonding force introduced through a specific surface modification process, so that the composite zinc microparticles can be firmly adsorbed on the surface of hydrophobic or hydrophilic substrates, and can withstand more than 20 water washing and wiping cycles. The silane coupling agent is selected from one or more combinations of γ-methacryloxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane or vinyltrimethoxysilane; The dispersant is a polycarboxylate superdispersant or a modified polyether dispersant, which is adsorbed on the surface of the composite zinc particles and prevents the nanoparticles from agglomerating through electrostatic repulsion and steric hindrance, thus ensuring the long-term storage stability of the slurry; the anti-settling agent is highly thixotropic organic bentonite or fumed silica. The benzalkonium chloride is dodecyl dimethyl benzyl ammonium chloride, which is a low-toxicity, low-irritant cationic surfactant; its addition amount is controlled below 0.05 parts, which is far lower than the concentration of conventional quaternary ammonium salt disinfectant.

[0007] Furthermore, the raw materials are composed of the following parts by weight: 1.5 parts of food-grade PA active composite zinc, 90 parts of deionized water, 1.8 parts of silane coupling agent, 0.7 parts of dispersant, 3 parts of anti-settling agent, 0.04 parts of benzalkonium chloride, 0.7 parts of thickener and 0.8 parts of defoamer.

[0008] A preparation process for a long-lasting disinfectant with physical barrier function includes the following steps: Step 1: Add deionized water and food-grade PA active composite zinc to a stainless steel reactor, mix the two, and stir for 5 minutes to obtain the basic solution; Step 2: Add wetting and dispersing agent and anti-settling agent to the base solution, continue stirring, and gradually increase the stirring speed; Step 3: Collect the suspension from the reactor in Step 2 and grind it using a nano-grinding machine; Step 4: After grinding, transfer the slurry and the ground suspension to a medium-speed mixing tank and stir at 500-800 rpm. Slowly add benzalkonium chloride and the remaining thickener and defoamer, and stir for 10 minutes to ensure that all components are completely dispersed and form a transparent homogeneous liquid. Step 5: While stirring, add silane coupling agent dropwise. After the addition is complete, continue stirring for 30 minutes to promote the condensation reaction between silane molecules and hydroxyl groups on the surface of zinc particles, thereby enhancing the adhesion of the subsequent film formation. Step 6: The mixture is filtered through a 500-600 mesh stainless steel filter to remove undispersed particles and mechanical impurities. The filtered liquid is then filled into clean containers under sterile conditions, sealed, and stored away from light to obtain the finished disinfectant solution.

[0009] Furthermore, in step one, the stirring speed in the reactor is 200–400 rpm.

[0010] Furthermore, in step two, the rotational speed is increased to 500-800 rpm.

[0011] Furthermore, in step three, the suspension grinding uses zirconia grinding media with a diameter of 0.5 mm, and the feed temperature is controlled to be no higher than 35°C.

[0012] Furthermore, in step three, the grinding is carried out continuously at a speed of 1200-1500 rpm for 8 hours. After grinding, the product is filtered through a 500-600 mesh filter. Cooling water is continuously circulated during the grinding process.

[0013] Furthermore, in step five, the dropping rate of the silane coupling agent is no greater than 5 mL / min.

[0014] Compared with the prior art, the present invention has the following beneficial effects: 1. The disinfectant prepared by this invention is suitable for various scenarios, such as object surfaces, fabrics, and air. It is effective against microorganisms such as pyogenic cocci, human coronaviruses, and influenza viruses. By continuously circulating cooling water during the grinding process, local overheating that could lead to component inactivation is prevented. A dual protection system is constructed through nano-grinding and silane coupling technology. This invention uses food-grade silanol-hydroxyl PA active composite zinc, under the action of a silane coupling agent, to form a physical barrier film with a nanoscale uneven structure on the object surface. By utilizing van der Waals forces to destroy the cell membrane of microorganisms, combined with the synergistic bactericidal effect of benzalkonium chloride, a 99.9% instant sterilization rate and a 72-hour long-lasting antibacterial effect are achieved.

[0015] 2. This invention employs distributed grinding and gradient stirring to ensure that the zinc particles are dispersed at the nanoscale. After precision filtration, the product stability is improved by 40%, and the film adhesion is enhanced by 35%. This disinfectant has no irritating odor and does not damage the skin or mucous membranes. It can be widely used in medical, food processing, and household applications, effectively solving the technical problems of short-lasting effects and easy development of drug resistance in traditional disinfectants. Attached Figure Description

[0016] Figure 1 This is a flowchart of the present invention. Detailed Implementation

[0017] The embodiments of the present invention will be described in further detail below with reference to the accompanying drawings and examples. The following examples are for illustrative purposes only and should not be construed as limiting the scope of the invention.

[0018] like Figure 1 As shown, the present invention provides a long-lasting disinfectant with physical barrier function, which is composed of the following raw materials in parts by weight: 0.5-2 parts of food-grade silanol-hydroxyl PA active composite zinc, 80-90 parts of deionized water, 0.5-2 parts of silane coupling agent, 0.5-1 part of dispersant, 2-4 parts of anti-settling agent, 0.04-0.05 parts of benzalkonium chloride, 0.5-1 part of thickener and 0.5-1 part of defoamer.

[0019] Food-grade silanol-hydroxyl PA active composite zinc is a composite microparticle made of porous silica as a matrix, loaded with active zinc ions through in-situ synthesis technology. The zinc element content is 15%–25% by mass, and the specific surface area is not less than 300 m².2 / g, particle size distribution controlled within the range of D50 = 200~500nm. Si-hydroxyl groups (Si-OH) refer to the abundant active silanol groups on the surface of the composite microparticles. These groups are not only anchoring sites for subsequent condensation reactions with silane coupling agents, but also key functional groups that impart hydrophilicity and reduce surface energy to the material. PA (Physical Adhesion) activity refers to active sites introduced through specific surface modification processes to enhance interfacial bonding, enabling the composite zinc microparticles to firmly adsorb onto hydrophobic or hydrophilic substrate surfaces, withstanding more than 20 water washes and wiping cycles.

[0020] The silane coupling agent is selected from one or more combinations of γ-methacryloxypropyltrimethoxysilane (KH-570), γ-aminopropyltriethoxysilane (KH-550), or vinyltrimethoxysilane. KH-570 is preferred because it contains unsaturated double bonds and methoxy groups, enabling it to undergo hydrolytic condensation with the hydroxyl groups on the surface of inorganic zinc particles and to entangle with organic polymer segments through double bonds, significantly improving the crosslinking density and mechanical strength of the film after formation.

[0021] The dispersant is a polycarboxylate superdispersant (such as TEGO Dispers 735W) or a modified polyether dispersant. Its main function is to adsorb onto the surface of the composite zinc particles, preventing nanoparticle aggregation through electrostatic repulsion and steric hindrance, thus ensuring the long-term storage stability of the slurry. The anti-settling agent is a highly thixotropic organobentonite or fumed silica. Its three-dimensional network structure effectively supports the suspension of solid particles and prevents sedimentation and stratification.

[0022] Benzalkonium chloride, or dodecyl dimethyl benzyl ammonium chloride, is a low-toxicity, low-irritant cationic surfactant. In this invention, its addition amount is strictly controlled to below 0.05 parts, far lower than the concentration of conventional quaternary ammonium salt disinfectants (usually 0.1%–0.2%). The aim is to utilize its electrostatic adsorption on negatively charged bacterial cell walls to assist physical barriers in rapid sterilization, rather than as the sole sterilization method, thereby significantly reducing the risk of drug resistance and ecotoxicity.

[0023] As one embodiment of the present invention, it is composed of the following raw materials in parts by weight: 1.5 parts of food-grade PA active composite zinc, 90 parts of deionized water, 1.8 parts of silane coupling agent, 0.7 parts of dispersant, 3 parts of anti-settling agent, 0.04 parts of benzalkonium chloride, 0.7 parts of thickener and 0.8 parts of defoamer.

[0024] This optimal formulation was derived through extensive orthogonal experiments. Under this formulation, the solid content of the composite zinc particles ensures that the micro-roughness of the film after formation is sufficient to pierce the bacterial wall, while avoiding excessive viscosity of the slurry due to excessive concentration, which would affect the spraying process. The amount of silane coupling agent is just enough to completely coat the surface of the zinc particles while leaving a small amount of free monomers to participate in film cross-linking, thus achieving the best balance of adhesion. The concentration of benzalkonium chloride is near the minimum effective inhibitory concentration (MIC), minimizing the amount of chemical agents used.

[0025] A preparation process for a long-lasting disinfectant with physical barrier function includes the following steps: Step 1: Add deionized water and food-grade PA active composite zinc to a stainless steel reactor, mix the two, and stir for 5 minutes to obtain the basic solution; The key to this step lies in controlling the feeding speed and the initial stirring rate. Because PA active composite zinc has a high specific gravity and surface energy, if poured into water quickly all at once, it easily forms "fish-eye" shaped agglomerates that are difficult to disperse later. Therefore, a "small amount, multiple times" approach should be used, adding the material while stirring, and utilizing a medium-low speed shear force of 200-400 rpm to initially wet the particles. The stirring time is set to 5 minutes to complete the pre-dispersion of the particles and avoid over-stirring the slurry.

[0026] Step 2: Add wetting and dispersing agent and anti-settling agent to the base solution, continue stirring, and gradually increase the stirring speed; This stage is the pre-stabilization stage of the slurry. The dispersant needs to be rapidly adsorbed onto the surface of the particles as soon as they deagglomerate, occupying steric hindrance sites. Increasing the rotation speed to 500-800 rpm is to provide sufficient shear force to break up soft agglomerates between powders. The stirring process needs to continue for 15-20 minutes until the slurry appears uniformly milky white, with no obvious dry powder floating or sediment. At this point, the absolute value of the Zeta potential is usually greater than 30 mV, indicating that the system is in a good kinetic stable state.

[0027] Step 3: Collect the suspension from the reactor in Step 2 and grind it using a nano-grinding machine; This is the core process that determines product performance. A horizontal nano-grinding mill is used, employing 0.5mm small-diameter zirconia beads as the grinding media, which have a high density (6.0 g / cm³). 3It exhibits strong wear resistance and does not react with zinc ions. The grinding speed is set at 1200~1500 rpm, with a linear velocity of 10~12 m / s, generating strong impact, shearing, and friction effects to strip the aggregates of composite zinc particles down to the primary particle size. Strictly controlling the feed temperature to not exceed 35℃ is crucial, as excessively high temperatures can intensify the movement of dispersant molecular chains, weakening their adsorption strength on the particle surface and even causing dispersant degradation and failure. An 8-hour grinding time ensures a narrow particle size distribution curve, with D90 controlled within 1μm. After grinding, a 500~600 mesh filter is used to intercept broken grinding bead fragments or large particle impurities, ensuring the purity of the slurry.

[0028] Step 4: After grinding, transfer the slurry and the ground suspension to a medium-speed mixing tank and stir at 500-800 rpm. Slowly add benzalkonium chloride and the remaining thickener and defoamer, and stir for 10 minutes to ensure that all components are completely dispersed and form a transparent homogeneous liquid. This step involves the compounding of functional additives. Benzalkonium chloride is a water-soluble cationic surfactant; its addition may cause flocculation with negatively charged dispersants. Therefore, the dropping rate must be controlled and the process carried out under high-speed stirring to ensure rapid dilution and uniform dispersion. The thickener is added to adjust the rheological properties of the final product, giving it suitable pseudoplasticity (shear-thinning characteristics) for easy spraying or wiping application. The defoamer is used to eliminate microbubbles generated during the preceding grinding process, improving the product's appearance and storage stability.

[0029] Step 5: While stirring, add silane coupling agent dropwise. After the addition is complete, continue stirring for 30 minutes to promote the condensation reaction between silane molecules and hydroxyl groups on the surface of zinc particles, thereby enhancing the adhesion of the subsequent film formation. This is a crucial step in the chemical reaction for constructing the physical barrier membrane. The silane coupling agent undergoes hydrolysis upon contact with water to generate silanol (Si-OH), which then undergoes dehydration condensation with the silanol groups on the surface of the composite zinc particles, forming Si-O-Si covalent bonds. Strict control of the dropping rate (≤5 mL / min) is to prevent excessively high local silane concentrations from causing self-condensation (forming polysiloxane precipitates), ensuring that the silane preferentially reacts with the inorganic particle surface to form a monolayer coating. The subsequent 30 minutes of stirring ensures the condensation reaction is complete, changing the particle surface from hydrophilic to hydrophobic, thus enhancing its flowability and spreadability during the drying and film-forming process.

[0030] Step 6: The mixture is filtered through a 500-600 mesh stainless steel filter to remove undispersed particles and mechanical impurities. The filtered liquid is then filled into clean containers under sterile conditions, sealed, and stored away from light to obtain the finished disinfectant solution.

[0031] Final precision filtration removes any trace gel particles or mechanical impurities that may have been generated during processing, ensuring the product's smoothness and transparency. The filling environment must meet GMP Class 100,000 cleanroom requirements to prevent microbial contamination. High-density polyethylene (HDPE) bottles are preferred for packaging due to their excellent barrier properties and chemical resistance. Storage away from light prevents photodegradation of the silane coupling agent caused by ultraviolet radiation, extending the product's shelf life.

[0032] In one embodiment of the present invention, in step one, the stirring speed in the reaction vessel is 200-400 rpm.

[0033] In one embodiment of the present invention, in step two, the rotation speed is increased to 500-800 rpm.

[0034] In one embodiment of the present invention, in step three, the suspension grinding uses zirconia grinding media with a diameter of 0.5 mm, and the feed temperature is controlled to be no higher than 35°C.

[0035] In one embodiment of the present invention, in step three, the grinding is carried out continuously at a speed of 1200-1500 rpm for 8 hours. After grinding, the material is filtered through a 500-600 mesh filter. Cooling water is continuously circulated during the grinding process.

[0036] In one embodiment of the present invention, in step five, the dropping rate of the silane coupling agent is no greater than 5 mL / min.

[0037] Adjust the concentration according to the application scenario: use the undiluted solution for disinfecting object surfaces, and dilute to a safe ratio for disinfecting skin and mucous membranes. Adding silane coupling agents improves the adhesion between the disinfectant and the substrate, ensuring the long-term effectiveness of the physical barrier; Example 1: When preparing a general-purpose disinfectant: Step 1: Add deionized water and food-grade PA active composite zinc to a stainless steel reactor, mix the two, and stir for 5 minutes to obtain the basic solution; Step 2: Add wetting and dispersing agent and anti-settling agent to the base solution, continue stirring, and gradually increase the stirring speed; Step 3: Collect the suspension from the reactor in Step 2 and grind it using a nano-grinding machine; Step 4: After grinding, transfer the slurry and the ground suspension to a medium-speed mixing tank and stir at 500-800 rpm. Slowly add benzalkonium chloride and the remaining thickener and defoamer, and stir for 10 minutes to ensure that all components are completely dispersed and form a transparent homogeneous liquid. Step 5: While stirring, add silane coupling agent dropwise. After the addition is complete, continue stirring for 30 minutes to promote the condensation reaction between silane molecules and hydroxyl groups on the surface of zinc particles, thereby enhancing the adhesion of the subsequent film formation. Step 6: The mixture is filtered through a 500-600 mesh stainless steel filter to remove undispersed particles and mechanical impurities. The filtered liquid is then filled into clean containers under sterile conditions, sealed, and stored away from light to obtain the finished disinfectant solution.

[0038] After grinding and filtration, it can be used directly for disinfection of object surfaces.

[0039] Example 2: For fabric disinfection, a thickener is added to the final product to enhance solution adhesion and ensure uniform coverage.

[0040] By amplifying the intermolecular forces on the material surface through physical modification techniques, a durable physical barrier is formed, thereby preventing microbial attachment and reproduction. It does not rely on chemical killing but achieves long-lasting protection through physical means, making it safe and less likely to induce drug resistance.

[0041] Fabric fibers have a rough, porous surface, making them susceptible to penetration by ordinary disinfectants. Ordinary disinfectants may penetrate the fibers, causing them to dry poorly or form a brittle crystalline layer on the fiber surface after drying, resulting in a stiff feel. This embodiment adjusts the rheological properties of the liquid by fine-tuning the thickener ratio, allowing it to spread better upon contact with the fabric without over-penetrating, while simultaneously forming a flexible, transparent protective film on the fiber surface. Testing showed that the treated cotton towels maintained a certain antibacterial rate even after repeated rubbing and washing, without affecting their absorbency and softness.

[0042] Example 3: Special liquid for air atomization disinfection Based on Example 1, the thickener and anti-settling agent components were removed, and the amount of dispersant was adjusted to 0.3 parts, while the remaining components remained unchanged. The precision filtration in step six was omitted during preparation (replaced with a 300-mesh filter) to reduce the risk of nozzle clogging. This special liquid has a low surface tension (<30mN / m) and atomized particle size concentrated between 10 and 50 μm, making it suitable for use with ultrasonic atomizers or aerosol sprayers. The atomized droplets can remain suspended in the air for more than 15 minutes, achieving a 99.5% inactivation rate against influenza virus (H1N1) in aerosols. The protective film formed on surfaces such as tabletops and handrails after settling shows no impact on antibacterial durability after wiping tests.

[0043] The embodiments of the present invention are given for the purposes of illustration and description. Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.

Claims

1. A long-lasting disinfectant with physical barrier function, characterized in that, Composed of the following raw materials in parts by weight: Food-grade silanol-hydroxyl PA active composite zinc, 0.5–2 parts; 80-95 parts deionized water; 0.5 to 2 parts of silane coupling agent; Dispersant 0.5 to 1 part; 2-4 parts anti-settling agent; 0.04–0.05 parts of benzalkonium chloride; Thickener 0.5 to 1 part; Defoamer 0.5 to 1 part; The food-grade silanol-hydroxyl PA active composite zinc is a composite microparticle with active zinc ions loaded onto a porous silica matrix through in-situ synthesis technology; wherein the zinc element accounts for 15% to 25% by mass, and the specific surface area is not less than 300 m². 2 / g, particle size distribution is controlled within the range of D50=200~500nm; silanol refers to the large number of active silanol groups on the surface of composite microparticles, PA activity refers to the active sites that enhance the interfacial bonding force introduced through a specific surface modification process, so that the composite zinc microparticles can be firmly adsorbed on the surface of hydrophobic or hydrophilic substrates, and can withstand more than 20 water washing and wiping cycles. The silane coupling agent is selected from one or more combinations of γ-methacryloxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane or vinyltrimethoxysilane; The dispersant is a polycarboxylate superdispersant or a modified polyether dispersant, which is adsorbed on the surface of the composite zinc particles and prevents the nanoparticles from agglomerating through electrostatic repulsion and steric hindrance, thus ensuring the long-term storage stability of the slurry; the anti-settling agent is highly thixotropic organic bentonite or fumed silica. The benzalkonium chloride is dodecyl dimethyl benzyl ammonium chloride, which is a low-toxicity, low-irritant cationic surfactant; its addition amount is controlled below 0.05 parts, which is far lower than the concentration of conventional quaternary ammonium salt disinfectant.

2. The long-lasting disinfectant with physical barrier function as described in claim 1, characterized in that, The product is composed of the following raw materials in parts by weight: 1.5 parts of food-grade silanol-hydroxyl PA active composite zinc; 90 parts deionized water; 1.8 parts of silane coupling agent; 0.7 parts dispersant; 3 parts anti-settling agent; 0.04 parts of benzalkonium chloride; Thickener 0.7 parts; 0.8 parts of defoamer.

3. A preparation process for a long-lasting disinfectant with physical barrier function as described in claims 1-2, characterized in that, Includes the following steps: Step 1: Add deionized water and food-grade PA active composite zinc to a stainless steel reactor, mix the two, and stir for 5 minutes to obtain the basic solution; Step 2: Add wetting and dispersing agent and anti-settling agent to the base solution, continue stirring, and gradually increase the stirring speed; Step 3: Collect the suspension from the reactor in Step 2 and grind it using a nano-grinding machine; Step 4: After grinding, transfer the slurry and the ground suspension to a medium-speed mixing tank and stir at 500-800 rpm. Slowly add benzalkonium chloride and the remaining thickener and defoamer, and stir for 10 minutes to ensure that all components are completely dispersed and form a transparent homogeneous liquid. Step 5: While stirring, add silane coupling agent dropwise. After the addition is complete, continue stirring for 30 minutes to promote the condensation reaction between silane molecules and hydroxyl groups on the surface of zinc particles, thereby enhancing the adhesion of the subsequent film formation. Step 6: The mixture is filtered through a 500-600 mesh stainless steel filter to remove undispersed particles and mechanical impurities. The filtered liquid is then filled into clean containers under sterile conditions, sealed, and stored away from light to obtain the finished disinfectant solution.

4. The preparation process of the long-lasting disinfectant with physical barrier effect as described in claim 3, characterized in that, In step one, the stirring speed in the reactor is 200-400 rpm.

5. The preparation process of the long-lasting disinfectant with physical barrier effect as described in claim 3, characterized in that, In step two, the rotation speed is increased to 500-800 rpm.

6. The preparation process of the long-lasting disinfectant with physical barrier effect as described in claim 3, characterized in that, In step three, the suspension grinding uses zirconia grinding media with a diameter of 0.5 mm, and the feed temperature is controlled to be no higher than 35°C.

7. The preparation process of the long-lasting disinfectant with physical barrier effect as described in claim 3, characterized in that, In step three, the grinding is carried out continuously at a speed of 1200-1500 rpm for 8 hours. After grinding, the product is filtered through a 500-600 mesh filter. Cooling water is continuously circulated during the grinding process.

8. The preparation process of the long-lasting disinfectant with physical barrier effect as described in claim 3, characterized in that, In step five, the dropping rate of the silane coupling agent shall not exceed 5 mL / min.